Morphometric analysis using geographical information system techniques in serpeng and sumurup watersheds - Septianingrum, R.S.; Haryono, E. (Institute of Physics, 2022)
Serpeng and Sumurup are allogeneic rivers in Wonosari’s basin, which derive water to Gunungsewu karst drainage system. The river flow characteristics of their allogeneic system are influenced by the watershed and weather conditions of the area. In addition, quantitative morphometry plays an important role in hydrological processes with remote sensing and geospatial techniques used to carry out a morphometric analysis. SRTM (DEM) was an efficient tool for extracting morphometric parameters. The watershed of the Sumurup river was much wider, and covers a total area of 42.80 km2, with a length of the main river being 21.44 km, while the Serpeng watershed covers an area of 10.58 km2 and length of the main river has 8.85 km. However, morphometry of the drainage density of both of them was classified on a medium category which indicates the basin is moderate permeability and has susceptible to flooding and erosion process. The highest order of Sumurup river has 4th level stream orders with has an elongated shape and Serpeng has 3rd level stream orders with an oval shape. Comparative analysis of watershed in the allogenic system could represent the geomorphological expression on the spatiotemporal variation of hydrology behavior of both rivers. © 2022 Institute of Physics Publishing. All rights reserved.